Terror of 10 MB, a cross-sectional study investigates the regulation to the prospective of medical device - Krishan Kumar Bhardwaj; K Bangarurajan; Tanveer Naved; Satyendra Kumar Rajput (Wolters Kluwer Medknow Publications, 2020)
An instrument, apparatus, implement, machine, implant, in vitro reagent, a component part or accessory which Intended for use in diagnosis of disease or other condition, or in the cure, mitigation and treatment or prevention of disease is called medical devices. Medical devices under new rule classified as Class A (low risk), Class B (low moderate risk), Class C (moderate high risk), and Class D (high risk) commemorating the notification of January 31, 2017 of Ministry of Health and Family Welfare which is conformity with Global Harmonisation Task Force framework. As per make in India program, the industry of medical devices is USD 5.2 billion and is contributing 4%-5% to the USD 96.7 billion Indian health-care industry. A total of 750-800 medical device manufacturers in India, an average investment of Rs 170-200 million and an average turnover of Rs 450-500 million. An online licensing portal of the Central Drugs Standard Control Organization (CDSCO) called "Sugam portal" has been launched on November 14, 2015, to file application and grant permission of registration exclusively for Medical Device CDSCO MD Online portal. By making the document submission easier, there are lot of challenges also present in "Sugam-online Portal." One of the main challenges in Sugam Portal is that there is no provision to upload files greater than 10MB file size. The current study addresses the issues and challenges faced by medical device industry and regulators with their potential solutions and recommendations.